STRATEGY OF DEVELOPMENT FOR PALM SUGAR BUSINESS AT UD. SARI AREN IN THE PERIOD AND POST- COVID-19 PANDEMIC THROUGH THE BUSINESS MODEL CANVAS (BMC) APPROACH - Oktoyoki, Hefri; Aprianto, Dodi; Yanuarti, Mira; Yulisa, Tri Anti Sukmala (Corolla International Conference, 2022)
UD. Sari Aren is one of the Aren agribusiness SMEs based in Rejang Lebong Regency. Economic growth and increased consumption of palm sugar in Indonesia and even globally have grown the MSME industry. So it has an attractive advantage and potential business opportunities. A business cannot be separated from weaknesses, obstacles and challenges, including UD. Sari Aren which experienced a very significant decline in sales during the pandemic. So, it takes the right business model and strategy to accelerate the development of the business. Thr purpose of reseach to: (1) identify the existing conditions owned by UD. Sari Aren is currently using the Business Model Canvas (BMC) approach, (2) analyzing the Strengths, Weaknesses, Opportunities and Threats (SWOT) of each element of BMC of UD. Sari Aren, (3) formulate a business development strategy that will be carried out by UD. Sari Aren is based on the refinement of the business model. This research was conducted using data collection techniques in the form of observation, interviews, and literature study. The data are analyzed by qualitatively. The results, obtained after identifying the nine elements of BMC and SWOT analysis, concluded that UD. Sari Aren needs improvement in the main resource elements (HR), product variations and key activities (marketing).